Carcass Characteristics, Organ Weights and Organoleptic Qualities of Broiler Finisher Birds Fed Potash Boiled Bambara Groundnut [Voandzeia subterranea (L) Thour] Meal as a Replacement for Soyabean Meal - Nwambe , R.N.; Omeje, S.I.; Isikwenu, J.O. (International Journal of Poultry Science, 2011)
Two hundred and twenty five (225) 28 day-old Anak broilers were randomly assigned to five treatment diets of 45 birds per treatment and replicated three times with 15 birds per replicate. Soyabean meal (full fat) was replaced with Potash Boiled Bambara Groundnut Meal (PBBGM) at 0, 25, 50, 70 and 100% levels. The diets were formulated to be isonitrogenous and isocaloric to provide 20% crude protein and 3000 kcal/kg metabolizable energy. At the end of the 4th week, one bird per replicate (3 birds per treatment) were randomly picked, fasted over night and slaughtered for carcass evaluation. The thighs of one bird per replicate were deboned and the tendons removed for organoleptic quality assessment. The results of the carcass characteristics indicated no significant differences (p>0.05) among the treatments for the weights of the various parts measured. On the cut-up parts, the percentage weights of the breast, back, drum-stick and thigh, showed significant differences (p<0.05) in all the treatment groups. There were significant differences (p<0.05) in the percentage weights of the spleen and gizzard; lengths of the proventriculus and the large intestine. The juiciness, flavour and overall acceptability of the broiler meat were not significantly (p>0.05) influenced by the treatments, thought the tenderness significantly (p<0.05) varied among the treatments.